Predicting cross-protection against foot-and-mouth disease virus strains by serology after vaccination - Gubbins, Simon; Paton, David J.; Dekker, Aldo; Ludi, Anna B.; Wilsden, Ginette; Browning, Clare F. J.; Eschbaumer, Michael; Barnabei, Jamie; Duque, Hernando; Pauszek, Lisa L.; King, Donald P. (Frontiers in Veterinary Science, 2022)
Serology is widely used to predict whether vaccinated individuals and populations will be protected against infectious diseases, including foot-and-mouth disease (FMD), which affects cloven-hoofed animals. Neutralising antibody titres to FMD challenge viruses correlate to protection against FMD, for vaccinated cattle that are infected with the same strain as in the vaccine (homologous protection). Similar relationships exist for cross-strain protection between different vaccine and challenge viruses, although much less data are available for these heterologous studies. Poor inter-laboratory reproducibility of the virus neutralisation test (VNT) also hampers comparisons between studies. Therefore, day-of-challenge sera (n=180) were assembled from 13 previous FMD cross-protection experiments for serotypes O (n=2), A (n=10) and SAT 2 (n=1). These were tested by VNT against the challenge viruses at the FMD FAO World Reference Laboratory (WRLFMD) and the titres were compared to challenge outcomes (protected or not). This dataset was combined with equivalent serology and protection data for 61 sera from four cross-protection experiments carried out at WRLFMD for serotypes O (n=2), A (n=1) and Asia 1 (n=1). VNT results and protection outcomes were also analysed for a serotype O cross-protection experiment involving 39 cattle, where the sera were not available for retesting at WRLFMD. Three categories of association between heterologous neutralising antibody titre and heterologous protection were found (Group 1-3). The log10 reciprocal titres associated on average with 75% protection (with 95% credible limits) were: Group 1: 2.46 (2.11-2.97); Group 2: 1.67 (1.49-1.92); Group 3: 1.17 (1.06-1.30). Further cross-protection data are needed to understand the factors that underpin this variability and to develop more robust antibody thresholds. Establishing cut-off serological titres that can be used to score the adequacy of vaccine-induced immunity will facilitate the monitoring and thereby the performance of FMD vaccination in the field.